2009
DOI: 10.1128/jvi.00593-09
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Transgene Expression Influences CD8+T-Cell Expansion and Maintenance following Immunization with Recombinant Adenovirus

Abstract: Previous studies determined that the CD8؉ T-cell response elicited by recombinant adenovirus exhibited a protracted contraction phase that was associated with long-term presentation of antigen. To gain further insight into this process, a doxycycline-regulated adenovirus was constructed to enable controlled extinction of transgene expression in vivo. We investigated the impact of premature termination of transgene expression at various time points (day 3 to day 60) following immunization. When transgene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 55 publications
4
77
0
Order By: Relevance
“…In an experiment in which naive transgenic T cells specific for the D8V epitope from B‐gal were transferred into previously vaccinated mice, expansion and proliferation of these (originally naive) cells could be seen even if transfer occurred 100 days after the original inoculation 16. This is consistent with data from our group and others showing persistence of adenoviral DNA and also vector‐derived transcripts over such long periods 34. Single‐cycle MCMV vectors interestingly also give similar results 35…”
Section: What Is Memory Inflation Now?supporting
confidence: 88%
“…In an experiment in which naive transgenic T cells specific for the D8V epitope from B‐gal were transferred into previously vaccinated mice, expansion and proliferation of these (originally naive) cells could be seen even if transfer occurred 100 days after the original inoculation 16. This is consistent with data from our group and others showing persistence of adenoviral DNA and also vector‐derived transcripts over such long periods 34. Single‐cycle MCMV vectors interestingly also give similar results 35…”
Section: What Is Memory Inflation Now?supporting
confidence: 88%
“…This means, that while it is likely that both direct and crosspresentation contribute in the induction of the response, it has until recently been unclear what is the relative contribution of each type of antigen presentation pathway, how this contribution may differ between different antigens and how this may affect the phenotypes of the responding T cells. Recent work by our group (Holst et al, 2010b) and the group of Jonathan L. Bramson (Bassett et al, 2011;Finn et al, 2009;Yang et al, 2006) has now begun to address this issue in greater detail.…”
Section: Tissue Transduction Propertiesmentioning
confidence: 99%
“…Notably, beyond 20 days post vaccination only extra-nodal expansion contributed to the T cell response. This method of antigen presentation is highly important during the early memory phase of the response as cessation of antigen expression by a doxycycline regulated vector drastically reduced the magnitude of late memory responses (Finn et al, 2009). Our tools did not allow detailed control of antigen expression, but we also observed a continuous expansion of memory T cells from 20 to 60 days post vaccination following high-dose i.v.…”
Section: The Issue Of Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Using a replication-deficient adenoviral vector, Tatsis et al (2007) demonstrated that the transgene product remains available for antigen presentation for as long as 16 weeks after a single immunizing dose. The importance of continuous transgene expression in the maintenance of the specific CD8 + T cells after AdHu5 vaccination was also demonstrated by a causal relationship between both using an inducible system to turn off the transgene expression (Finn et al, 2009). Bassett et al (2011) showed that both hematopoietic and non-hematopoietic antigenpresenting cells are necessary for the maintenance of CD8 + T cells following immunization with recombinant adenovirus.…”
Section: Refractoriness To Apoptosis Of Specific Cd8 + T Cellsmentioning
confidence: 99%